Stomatitis Healing via Hydrogels Comprising Proline, Carboxyvinyl Polymer, and Water - Raichi Hanaki; Koji Harada; Yoshihiro Sasaki; Michiaki Matsumoto; Yoshiro Tahara (Gels)
Chemotherapy using anticancer agents and radiotherapy of cancers frequently induce the development of stomatitis as a side effect. In the present study, hydrogels for effective stomatitis healing under anticancer drug administration were developed using three components, namely proline, carboxyvinyl polymer, and water (denoted proline gels). Characterization including tilting, Fourier transform infrared spectra, and viscoelasticity measurements indicated that proline gels with proline concentrations over 300 μmol/g could retain water on the tongue of mice. The degradation and release behavior of proline gels in serological environments were evaluated, revealing that proline gels were degraded by serological salt concentrations, and the cumulative amount of proline released from proline gels depended on the concentration of proline in the gel. Proline gels were applied to the stomatitis area on the tongue of mice under anticancer drug administration, with subsequent reduction in the stomatitis area and regeneration of the mucosal epithelium layer, demonstrating effective stomatitis healing by proline gels with proline concentrations over 500 μmol/g. Other control samples including the carboxyvinyl polymer or proline alone did not reduce the stomatitis area in model mice. These results suggested that the proline gel is promising for the mucosa regeneration of anticancer drug-induced stomatitis.